Hubungan antara Experiential Marketing, Layanan Restoran Prasmanan, Customer Satisfaction, dan Customer Loyalty - Grace Chintia Sutanto; Tias Andarini Indarwati (Jurnal Ilmu Manajemen, 2020)
Every company wants its brand to be a major concern for consumers. Experiential marketing is a way of marketing that not only sells products but also creates them accompanied by emotional experiences that touch consumers' hearts. One of the businesses that are using experiential marketing is Hanamasa Restaurant which is a Japanese restaurant with buffet service type. The purpose of this research is to investigate the effect of experiential marketing and service attributes on buffet restaurants on customer loyalty with customer satisfaction as a mediating variable, a case study of Hanamasa consumers in Surabaya. Path analysis using AMOS 24 and IBM SPSS was performed for statistical analysis. Research with 110 respondents was taken with nonprobability sampling techniques. Criteria for respondents in this study are at least 19 years old and have visited Hanamasa at least twice in the past one to six months. The results of this study are experiential marketing a positive effect on customer satisfaction both through customer loyalty and directly. Likewise, the effect of service attributes on buffet restaurants has a positive impact on customer satisfaction but not on customer loyalty.